Pengaruh Content Marketing Dan Kualitas Produk Terhadap Keputusan Pembelian Di Aldyan Store - Deta, Veronica Aprilia Avista; Rangga, Yoseph Darius Purnama; Valeria Eldyn Gula (Universitas Nusa Nipa Maumere, 2026)
This study aims to examine the influence of Content Marketing and Product Quality on Purchase Decisions among consumers of Aldyan Store. The research employed a quantitative method with a survey approach. The population consisted of Aldyan Store consumers, with a sample of 100 respondents selected using a sampling technique appropriate to the characteristics of the study. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), t-test, and F-test with the assistance of SPSS version 23. The results showed that, partially, Content Marketing had a positive and significant effect on Purchase Decisions, with a t-value of 2.544 and a significance level of 0.013 < 0.05. Product Quality also had a positive and significant effect on Purchase Decisions, with a t-value of 2.288 and a significance level of 0.024 < 0.05. Simultaneously, Content Marketing and Product Quality had a positive and significant effect on Purchase Decisions, with an F-value of 9.358 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) was 0.162, indicating that Content Marketing and Product Quality explained 16.2% of the variance in Purchase Decisions, while the remaining 83.8% was influenced by other factors outside the research model. Based on the findings, it can be concluded that Content Marketing and Product Quality play an important role in improving consumers' Purchase Decisions at Aldyan Store. Therefore, Aldyan Store should continue to enhance the quality of its marketing content and maintain product quality to increase consumer trust and purchase intention.